Convergence of Indigenous Knowledge Systems and Sustainable Agriculture: Socioeconomic, Policy, and Agribusiness Perspectives - Albert Thembinkosi Modi (Program Studi Magister Agribisnis, Universitas Sebelas Maret, 2026)
Global agricultural systems face increasing pressures from climate change, biodiversity loss, and socio-economic inequalities, necessitating integrative and context-specific approaches. This study examines the convergence of Indigenous Knowledge Systems (IKS) and scientific agriculture through a three-pillar framework: Environmental Management, Classification of Knowledge, and Agricultural Sustainability. A qualitative synthesis of literature, policy documents, and case studies (2000–2025) was conducted using thematic and agroecological perspectives. The study advances an integrated Indigenous–scientific production model that incorporates biophysical factors, management inputs, and an Indigenous Knowledge Index (IKI) to quantify experiential knowledge. Scenario-based comparisons of indigenous-only, scientific-only, and integrated systems reveal that hybrid approaches enhance productivity, resilience, and resource-use efficiency while reducing dependency on external inputs. Indigenous systems contribute significantly to climate adaptation and biodiversity conservation, whereas scientific systems support yield optimization and scalability. However, the marginalization of IKS within dominant policy and institutional frameworks remains a critical barrier to integration. The findings highlight that participatory approaches, knowledge co-production, and decision-support tools are essential for operationalizing integration. The study concludes that convergence between Indigenous and scientific knowledge systems provides a practical and scalable pathway for sustainable intensification, inclusive agribusiness development, and rural socioeconomic empowerment.